A critical look at declining rate filtration design - (:unkn) unknown (Elsevier Sci Ltd, Exeter, 1998)
Current design methods for declining rate filtration (DRF) utilize data obtained from pilot or full-scale constant rate filtration (CRF) plants. One of the key questions that must be answered is the following: What is the rise in the water level between backwashes in the operation of a DRF plant? Cleasby and his coworkers made the experimental observation that 'the slope of the head loss curve for a bank of several DR filters operating at a particular average rate was the same as the slope for a CR filter operating at the same rate.' This observation, if accepted to be generally valid, makes possible the estimation of the mentioned water level rise using CRF data only. This paper presents a theoretical examination of the experimental observation of Cleasby and his coworkers and the water level calculation method that is based on it. The conditions under which the method may be valid are delineated. While DRF is reported to be a better filter control method than mechanical CR filtration methods, a lack of good understanding of its unique features and the absence of easily usable and generally applicable design methods have prevented its more widespread utilization. This paper should contribute to a better understanding of DRF and lead to further research for the development of new design methods.Current design methods for declining rate filtration (DRF) utilize data obtained from pilot or full-scale constant rate filtration (CRF) plants. One of the key questions that must be answered is the following: What is the rise in the water level between backwashes in the operation of a DRF plant? Cleasby and his coworkers made the experimental observation that 'the slope of the head loss curve for a bank of several DR filters operating at a particular average rate was the same as the slope for a CR filter operating at the same rate.' This observation, if accepted to be generally valid, makes possible the estimation of the mentioned water level rise using CRF data only. This paper presents a theoretical examination of the experimental observation of Cleasby and his coworkers and the water level calculation method that is based on it. The conditions under which the method may be valid are delineated. While DRF is reported to be a better filter control method than mechanical CR filtration methods, a lack of good understanding of its unique features and the absence of easily usable and generally applicable design methods have prevented its more widespread utilization. This paper should contribute to a better understanding of DRF and lead to further research for the development of new design methods.
Keywords: Declining rate filtration; Filtration; Wastewater treatment; Water treatment